Impact of Social Media Websites Overuse on Mental Well Being of Medical Students - Sumbal Khalid, Usman Amin Hotiana, Zunaira Muzzamil, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Social media over usage is becoming an addictive behaviour in medical students. This excessive use of social media websites is compromising the mental health of the medical students. Aim: To find the relation of social media overuse on mental well being of medical students. Study design: Cross-sectional study. Methodology: Third, Fourth and fifth year MBBS students of Akhtar Saeed Medical and Dental college, Lahore were included in the current study. 230 Questionnaires were distributed among the students. The questionnaire was in two parts. In one part 10 questions were asked, related to five famous social media websites usage. The second part of the questionnaire contained Kessler psychological distress scale. Out of 230 students, 195 students filled the questionnaires. Data was evaluated by using SPSS version 20. Results: Majority of the students (42 %) were turned out to be severely distressed. 37% students were doing well while 28% and 16% students had mild and moderate distress. All of the severely distressed students used facebook, instagram and watsapp. 98.43% students used snapchat and 82.81 % students used tiktok. Those with severe distress, were found to spend more than 1 hour per day on social media websites. Conclusion: It was concluded that there is a strong correlation of the time spent on social media with the mental well being of medical students. More time spent on social media had led to more mental distress in medical students. Keywords: Social Media, Medical Students, Mental Health and Mental Distress.